APLIKASI PEMBENAH TANAH PADA BIDANG PERTANIAN DI INDONESIA: DESIGN RISET DAN ANALISIS DATA - Dwitia, Yosi; Dulbari, Dulbari; Subarjo, Subarjo (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2025)
Soil fertility is a key factor in agricultural success; however, poor soil quality often hindersproductivity. One solution is the use of soil amendments to improve soil's physical, chemical,and biological properties. This study aims to analyze research trends on soil amendments inIndonesia based on agricultural journals from 2015 to 2024. Data were collected throughGoogle Scholar, with a total of 24 articles analyzed based on publication count, research design,indicator plants, treatments, and data analysis methods used. The analysis results indicatefluctuations in research trends, with the highest number of publications in 2021 and 2022. The Factorial Randomized Block Design was the most commonly used method, while the mostfrequently studied indicator plants were soybean, rice, and maize. The most common treatmentinvolved combining soil amendments with organic and inorganic fertilizers. The dominant dataanalysis method was ANOVA, followed by post hoc tests such as LSD and Tukey HSD todetermine significant differences between treatment groups. This study recommends furtherresearch on the effectiveness of soil amendments in supporting sustainable agriculture andexploring their use across various plant species and environmental conditions.